SCREENING OF ANTITUBERCULAR ACTIVITY OF SOME MEDICINAL PLANTS FROM WESTERN GHATS, INDIA - M. MUTHUSWAMY; PRABUSEENIVASAN; VANAJA KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Tuberculosis (TB) is an infectious disease caused by the bacterium, Mycobacterium tuberculosis (MTB). Uncontrolled usage of existing drugs the number of cases of tuberculosis throughout the world has been increasing rapidly, due to the emergence of Multi-drug resistant MTB strains, there is a need for new and novel sources of antimycobacterial drugs especially from the natural products. In this study, methanol extract of 32 medicinal plants were screened against M. tuberculosis H37Rv, multi drug resistant (MDR) and sensitive strains to all first line drugs by rapid method luciferase reporter phage (LRP) assay. Plants were selected based on information collected from tribal people of Western Ghats at Tirunelveli district. Two concentrations viz. 100µg and 500µg were used for screening to identify the effective medicinal plant for antimycobacterial activity. Among the thirty two plants tested, seven plants were showed potent activity against the tested organisms at 500µg/ml concentration. However Ruta graveolens extract exhibited good antimycobacterial activity against all the tested strains M. tuberculosis H37Rv (76.60%), MDR, (87.25%) and Sensitive strains and (94.32 %) even at lower concentration (100µg/ml). Remaining plants showed moderate or no activity.